Hubungan Antara Persepsi Terhadap Gaya Kepemimpinan Partisipatif Dengan Komitmen Organisasi Karyawan - Hidayat, M. Lutfi Khoerudin, Yudhi Satria Restu, S.E., S.Psi., M.Si (2015)
Human Resources (HR) is the key factor of the many sources of potential support the success of an organization. They are members who have a consistent commitment to motivate themselves at a certain level to perform in accordance with the duties and functions within the organization. There are several factors that can influence the rise and fall of a person's commitment to the organization that is the perception and the application of participative leadership style by the company. The purpose of this study are: 1) to determine the relationship between perceptions of participative leadership style and organizational commitment of employees. 2) to determine the level of employee perceptions of participative leadership style. 3) to determine the level of organizational commitment of employees. 4) to determine the effective contribution of perceptions of participative leadership style on employees' organizational commitment. The hypothesis of this study is that there is a positive relationship between perceptions of participative leadership style and organizational commitment of employees. The sampling technique used was purposive non-random sampling. Methods of data collection using the scale perception towards participative leadership style and organizational commitment scale employees. Data were analyzed using product moment correlation. Based on the analysis product moment correlation coefficient r xy values ​​obtained for = 0.623; p = 0.000 (p <0.01) means that there is a very significant positive correlation between perceptions of participative leadership style and organizational commitment of employees. The effective contribution of these two variables is shown by the determinant coefficient (r2) equal to = 0.388 showing the variable perceptions of participative leadership style affects organizational commitment of employees amounted = 38.8% and 61.2% were influenced by other variables. The conclusion from this study is that there is a very significant positive relationship between perceptions of participative leadership style and organizational commitment of employees